Vocational Teachers Perception of Teaching Staff, Program Content Selection and Finance Responsibility - Hendarman Hendarman (Universitas Negeri Malang, 2016)
The study was intended to find out the perception of technical and vocational teachers of teaching staff, institutions authorised for program content selection and parties responsible for the financing of technical and vocational education (TVE) in the context of Indonesia. The respondents were randomly selected from government technical and vocational schools and consisted of 120 and 100 teachers from West Java and South Sulawesi. The study revealed that: to teach in technical and vocational schools somebody must have teaching and work experience in the same area of teaching; to design the program teachers and industry people must work together; and to finance the operation and maintenance of TVE the government must work with the private sector.